2009
DOI: 10.1016/j.carj.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Guided Vacuum-Assisted Breast Biopsy: An Initial Experience in a Community Hospital

Abstract: This study demonstrated that detection of cancerous and high-risk lesions can be significantly increased when an MRI-guided biopsy program is introduced at a community-based hospital. We believe that as radiologists gain confidence in imaging and histologic correlation, community-based hospitals can achieve similar rates of occult lesion diagnosis as those found in data emerging from academic institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
3
1
Order By: Relevance
“…Both frequency of high-risk lesions at MRgVABB and underestimation rates in our study are higher than previously reported in other studies (Table 4) evaluating outcomes of MR-guided breast biopsy [11,12,29,31,32]. This might be explained by the high pretest probability for breast cancer in our study population, which in addition to asymptomatic women undergoing screening MRI included a substantial proportion of diagnostic cases and patients with a personal history of breast carcinoma.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Both frequency of high-risk lesions at MRgVABB and underestimation rates in our study are higher than previously reported in other studies (Table 4) evaluating outcomes of MR-guided breast biopsy [11,12,29,31,32]. This might be explained by the high pretest probability for breast cancer in our study population, which in addition to asymptomatic women undergoing screening MRI included a substantial proportion of diagnostic cases and patients with a personal history of breast carcinoma.…”
Section: Discussioncontrasting
confidence: 71%
“…Moreover, MRI of the breast is superior not only for diagnosis of invasive carcinoma but also for detection of ductal carcinoma in situ (DCIS) and even premalignant breast lesions [4,5]. MRI-guided vacuumassisted breast biopsy (MRgVABB) is a safe and accurate technique for evaluation of otherwise occult MRI-detected breast lesions [6][7][8][9][10][11][12]. However, a considerable proportion of lesions diagnosed on percutaneous breast biopsies are classified as high-risk lesions [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach resulted in a rate of change of surgical planning inferior to 10%, composed of mastectomy for lesions [24], many recent single-center experiences [25][26][27][28][29][30][31], also evaluating problems and limitations [32][33][34][35], as well as the results of a multidisciplinary consensus meeting on the use of vacuum-assisted MR-guided biopsy [36]. The mean time needed for an MR-guided procedure is not different than that of a stereotactic biopsy in the film-screen era: about 45 minutes [37].…”
Section: Additional Findings At Preoperative Mri a Simple Golden Rulmentioning
confidence: 99%